علاقة استراتيجيات مواجهة الضغوط بالإكتئاب - جلاب, محمد; ايت مولود, يسمينة (جامعة الوادي - University of Eloued, 2022)
The current study aimed to know the relationship between coping strategies, and the degree of depression among nurses of Urgency Department , it was applied a random sample of '100' nurses. The researcher Wakly Badia’s questionnaire of coping strategies (2014), and Beck Depression Scale (BDI2) were applied. Result :There is a correlation between the strategies of coping with stress and the degree of depression among nurses. The nurses use the most effective coping strategies in facing stress.- There are differences in the coping strategies, and in the degree of depression among nurses due to gender.
لدى ممرضي مصلحة الإستعجالات
مقال
Keywords: استراتيجيات,ممرضين,الاكتئاب,مواجهة الضغوط; coping strategies; depression; nurses